2016
DOI: 10.1021/acs.organomet.6b00239
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of NHC-Oxazoline Pincer Complexes of Rh and Ru and Their Catalytic Activity for Hydrogenation and Conjugate Reduction

Abstract: We describe the preparation and catalytic reactions of new CCN pincer Rh and Ru complexes containing NCH-oxazoline hybrid ligands. Oxazolinyl-phenyl-imidazolium derivatives (3) were suitable ligand precursors for the CCN pincer scaffold. C−H bond activation of 3 with RhCl 3 • 3H 2 O in the presence of NEt 3 yielded the desired CCN pincer Rh complexes 5 in 13−27% yields. The related CCN pincer Ru complexes 8−10 were synthesized in good yields by C−H bond activation of p-cymene Ru complexes 7 in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 89 publications
0
16
2
Order By: Relevance
“…In spite of the loss of p-cymene moiety, the mechanism of ATH probably involved, also in this case, a classical catalytic cycle. [37][38][39][40] Taking into consideration the differences in both structural coordination mode, our complexes resulted less active and straightly less stereoselective in comparison with other similar catalytic systems reported in literature. 16,35,[41][42] In those systems better results might depend on the presence of an additive in formation of bimetallic 6-membered transition state or in alternative on the presence of an additional phosphine ligand known for reducing the acidity of metal center that favors the hydride transfer.…”
Section: N-(3r4r)-3-[(s)-2-(aminomethyl)pyrrolidin-1-yl]-1-benzylpipmentioning
confidence: 57%
See 1 more Smart Citation
“…In spite of the loss of p-cymene moiety, the mechanism of ATH probably involved, also in this case, a classical catalytic cycle. [37][38][39][40] Taking into consideration the differences in both structural coordination mode, our complexes resulted less active and straightly less stereoselective in comparison with other similar catalytic systems reported in literature. 16,35,[41][42] In those systems better results might depend on the presence of an additive in formation of bimetallic 6-membered transition state or in alternative on the presence of an additional phosphine ligand known for reducing the acidity of metal center that favors the hydride transfer.…”
Section: N-(3r4r)-3-[(s)-2-(aminomethyl)pyrrolidin-1-yl]-1-benzylpipmentioning
confidence: 57%
“…Furthermore, the results obtained with our complexes, indicated that the steric hindrance around the Ru center in the transition state, deriving both from the ligand and the substrate, could affect the reactivity and the enantioselectivity of the reactions. 27,37 In summary, the best result in terms of reaction rate and enantioselectivity was obtained with complex A in the reduction of the activated ketone substrate 4f, ethyl 3-oxo-3phenylpropanoate (entry 22).…”
Section: N-(3r4r)-3-[(s)-2-(aminomethyl)pyrrolidin-1-yl]-1-benzylpipmentioning
confidence: 99%
“…These results suggest that further development of these mixed-carbene-oxazoline systems could be useful for the selective reduction of extended aromatic-ring-systems. 204 …”
Section: Mono(oxazoline) Ligandsmentioning
confidence: 99%
“…To avoid decarbonylation, employment of carbonyl Ru catalysts has been investigated. , In the past decade, monocarbonyl ruthenium complexes have been successfully applied in a number of organic reactions, such as TH and HY of carbonyl compounds, HY of carboxylic and carbonic acid derivatives, alcohol dehydrogenation, and C–X (X = C, N) forming reactions . Relevant examples of monocarbonyl catalysts are [Ru­(TFA) 2 (PPh 3 ) 2 (CO)], [Ru­(μ-OCOC 2 F 4 OCO)­(diphosphine)­(CO)] 2 , [Ru­(OAc)­(CCN)­(CO)], Ru­(CNO)­(PPh 3 ) 2 (CO)], [RuCl 2 (NNN)­(CO)] and [RuCl­(NNN)­(HOCH 3 )­(CO)]­Cl, and those reported by Milstein ([RuH­(PNN)­(CO)]), Gusev ([RuCl 2 (PNN)­(CO)]), and Saito ([RuHCl­(PNN)­(CO)]) . Moreover, we have described that the derivatives [RuCl­((2-CH 2 -6-MeC 6 H 3 )­PPh 2 )­(NN)­(CO)] and [RuH­(Ph 2 P­(CH 2 ) 3 PPh 2 )­(NN)­(CO)]­Cl (NN = en, ampy) are active in ketone TH reactions.…”
Section: Introductionmentioning
confidence: 99%